ANALYZING FOREIGN LANGUAGE LISTENING ANXIETY AND ONLINE ENGLISH PROFICIENCY TEST OF UNDERGRADUATE STUDENTS - Sufiyah Dueraseh; Dodi Mulyadi; Testiana Deni Wijayatiningsih (Universitas Muhammadiyah Semarang, 2021)
Listening is the key to communication; if the students do not master it, they lose confidence and worry until listening to anxiety. This research explained about Analyzing foreign language listening anxiety and Online English proficiency test of undergraduate students at University of Muhammadiyah Semarang in which it aims to know the relationship between foreign language listening anxiety and listening proficiency test scores and to figure out the factors that influence undergraduate students' anxiety while doing a listening proficiency test. This research used explanatory sequential mixed methods design (also called a two-phase model) means finding two data in the same target. The instruments were collected by using a questionnaire and an interview. The collected data were analyzed using SPSS (17.0) software in percentage, R-square, and significance. The subject of this thesis was 101 undergraduate students at Muhammadiyah Semarang University. The results of this research were 1) foreign language listening anxiety and English proficiency test were only number four that was the relationship. It was anxiety bothering them to encounter a word they could not pronounce while listening to English, such as when the anxiety came to their mind; they would panic and stress; 2) The factors that made the undergraduate students were anxiety in the listening proficiency test. Most of them were a panic, worry, and led them to be stressed and anxious in doing a listening test.